PENGARUH TEACHER FEEDBACK TERHADAP KEMAMPAUN MURID DALAM PEMBELAJARAN WRITING - Muh Arief Muhsin; Ika Sastrawati (JURNAL KONFIKS, 2016)
ABSTRACT The research aimed to describe the phenomena of feedback given by the teacher in learning writing. In addition, this study was also described how the response given by the student when receiving feedback from the teacher. The long term goal to be achieved was the improvement of the teaching system so that every educational institution had aimed at teaching concepts to form an intelligent generation. This study was a descriptive qualitative research to be carried out in SMA Muhammadiyah 1 Unismuh Makassar which one of top schools Muhammadiyah. The ability of students in the school had been considered good in communication, but their ability to write was still lacking , especially in terms of grammatical . Therefore, the researcher was described the feedback given by the subject teachers of English subjects at the time of writing , especially when students learned making mistakes in the process of teaching and learning in the classroom . The extent, the teacher can give feedback to the students.  The research was described the positive feedback and negative feedback given by the teacher so that it can be information and feedback in the learning process.Giving feedback subject teachers more English language based situation in the classroom. In writing instructional materials for example, most teachers use an explicit correction and metalinguistic feedback. This is because students are using written language than spoken language. Almost kinds of feedback used in teaching but not as often as with the two types of feedback. The students have different conditions, but most were more likely to agree given feedback after speaking or after making a mistake. The most powerful reason is the lack of experience of students in learning English so want to get direct feedback.Key words: Teacher Feedback, murid, Writing ABSTRAKPenelitian ini bertujuan untuk menggambarkan fenomena umpan balik yang diberikan oleh guru dalam belajar menulis. Selain itu, penelitian ini juga menggambarkan bagaimana respon yang diberikan oleh siswa saat menerima umpan balik dari guru. Tujuan jangka panjang yang ingin dicapai adalah peningkatan sistem pengajaran sehingga setiap lembaga pendidikan telah ditujukan untuk konsep mengajar untuk membentuk generasi yang cerdas. Penelitian ini merupakan penelitian deskriptif kualitatif yang akan dilaksanakan di SMA Muhammadiyah 1 Unismuh Makassar yang salah satu sekolah top Muhammadiyah. Kemampuan siswa di sekolah telah dianggap baik dalam komunikasi, tetapi kemampuan mereka untuk menulis masih kurang, terutama dalam hal tata bahasa. Oleh karena itu, peneliti digambarkan umpan balik yang diberikan oleh guru mata pelajaran mata pelajaran bahasa Inggris pada saat menulis, terutama ketika siswa pelajari membuat kesalahan dalam proses belajar mengajar di kelas. Sejauh ini, guru dapat memberikan umpan balik kepada siswa. Penelitian ini menggambarkan umpan balik positif dan umpan balik negatif yang diberikan oleh guru sehingga dapat menjadi informasi dan umpan balik dalam proses pembelajaran.Memberikan umpan balik guru mata pelajaran situasi berdasarkan bahasa lebih Inggris di dalam kelas. Dalam menulis bahan ajar misalnya, sebagian besar guru menggunakan koreksi eksplisit dan umpan balik metalinguistik. Hal ini karena siswa menggunakan bahasa tertulis dari bahasa lisan. Hampir jenis umpan balik yang digunakan dalam mengajar tapi tidak sesering dengan dua jenis umpan balik. Para siswa memiliki kondisi yang berbeda, tetapi kebanyakan lebih cenderung setuju diberikan umpan balik setelah berbicara atau setelah melakukan kesalahan. Alasan paling kuat adalah kurangnya pengalaman siswa dalam belajar bahasa Inggris sehingga ingin mendapatkan umpan balik langsung. Kata kunci: Guru Feedback, murid, Menulis